Women and Poverty: Case Study of Female Labor (TKW) in Indramayu Regency - Dewi Nurmalasari (Penerbit Hellow Pustaka, 2024)
Women are often paired with poverty problems, structural and cultural obstacles seem to never stop entangling them. The choice to become a migrant worker has become a dream of a decent and prosperous life that for him cannot be relied on by anyone, including the government. With a more dominant economic background and low human resources, women are often powerless to get out of the problems that come to them. Even though it is widely depicted in the media about the grim portrait of migrant workers in various cases, the number of migrant workers continues to increase from year to year. Some of the underlying points are that the employment opportunities available at home are limited and labour wages abroad are much higher than those at home. As the second largest contributor of foreign exchange after oil and gas, TKW should receive more attention, including its rights to obtain protection as a citizen